Influence of amino acids, and their interaction with volatiles and polyphenols, on the sensory properties of red wine. (27th July 2022) - Espinase Nandorfy, D.; Watson, F.; Likos, D.; Siebert, T.; Bindon, K.; Kassara, S.; Shellie, R.; Keast, R.; Francis, I.L.
Abstract: Background and Aims: The effect of amino acids, and their interactions with volatiles and other non‐volatiles, on in‐mouth sensory properties of red wines is not known. This knowledge gap has been studied in a series of comprehensive sensory experiments. Methods and Results: A solvent‐assisted flavour evaporation extract of Shiraz wine volatiles, a de‐aromatised polyphenolic extract and amino acids were added to model wine and wine systems. Using full factorial designs, samples were evaluated by sensory quantitative descriptive analysis. Volatiles enhanced Viscous mouthfeel ( F  = 20.0, P  < 0.001), Sweetness ( F  = 26.5, P  < 0.001) and Body ( F  = 81.4, P  < 0.001), while the phenolic extract directed Astringency ( F  = 170.5, P  < 0.001) as well as Bitterness ( F  = 7.3, P  < 0.001) and suppressed Sweetness ( F  = 16.5, P  < 0.001). An amino acid by volatile interaction ( F  = 4.2, P  < 0.05) was found, and further experiments showed that L‐proline enhanced Viscosity ( F  = 5.0, P  < 0.05), Sweetness ( F  = 14.4, P  < 0.001), Red fruit flavour ( F  = 7.8, P  < 0.001) and suppressed Astringency ( F  = 6.1, P  < 0.05) and Bitterness ( F  = 7.0, P  < 0.01), while L‐glutamic acid imparted an Umami taste ( F  = 5.0, P  < 0.05) at wine‐like concentration. Conclusions: For the first time, these causal experiments showed that amino acids can influence the taste, mouthfeel and flavour of red wine. Significance of the Study: This work provides insight into a new class of wine compounds of sensory significance that can be targeted by producers to directly influence wine flavour.